Cognitive development in children: a pivotal ladder towards successful maturation – an overview - Ghosh, Debadrita; Mukherjee, Chitrita Gupta (International Journal of Contemporary Pediatrics, 2026)
This paper depicts an overview by correlating Piaget's theory of ‘cognitive development’ with several ‘psychological’ perspectives of development during the various stages of life; with the onset, beginning, right from birth extending upto late adolescence. Chiefly, the far- improved, imaginary, magnificently integrated nature of mental representations, with its broad levels of development and maturation; associated with the humans during this tenure can be well appreciated. The ‘cognitive model’ as described by Jean Piaget also demonstrates a strong connection with the subsequent behavior management techniques in children. Piaget theorized that children's knowledge about reality is realized by ‘touching’ and ‘observing’; he termed this phenomenon as ‘constructivism’. Though, through the massive evolution of time, the ‘theory of cognition’ has suffered a waning of influence, because of it’s gross list of short-comings and drawbacks, yet it remains one of the most sought-after concepts, even to this day, because of its impeccable contributions to the arena of both physical and mental maturation.